Rekayasa Dan Pengembangan Perpustakaan Digital Menggunakan Codeigniter Dengan Metode Pengembangan Perangkat Lunak Scrum - M Masrur Rofi, Arfany; I GL Putra Eka , Prismana; Muhammad Fatkhur , Rizal (Inovate, 2022)
Libraries as information providers and information managers at this time, should follow the flow of changes in information technology in this digital era. libraries no longer have to be traditional or manual in providing various information services to their members. Libraries in several universities have begun to implement library functions that were previously traditionally or manually processed to be automated until later a new term, online or digital library, emerged. With the existence of digital information that can be done with a computerized system known as OPAC (online Access Cataloging). OPAC is the output of the information retrieval system. Search results conducted through the tool provide satisfaction for the user. The method used in solving this problem is the Scrum method. Scrum is an agile and software development framework agile addition to software projects and managing product or application development. In the Scrum method there are 3 roles in the process, Product Owner (As Client), Scrum Master (As a Supervisor and Evaluating Developer Performance, Developer (Project Maker).The results of this study include the development of a digital library using Codeigniter framework with the Scrum method. In developing the system, it runs well and produces satisfying results for the writer. The use ofthe Scrum method is also very appropriate because of the supporting factors from various Hasyim Asy’ari University librarians who provide support in the from of suggestions for adding various features to the digital web library as a from of futher development so that a more dynamic digital library can be achieved.Keywords : Digital Library, Design, Information, Web